Is German Measles Really Uncommon in our Comminuty? A Report from Personal Observation - Rahman, MK; Alim, MA; Chowdhury, MMH; Khan, MMR; Rashid, M Harun Or; Khanom, K; Mahmood, I (TAJ: Journal of Teachers Association, 2010)
Although German Measles is a mild exanthematous illness, because of the immense teratogenic potential of the virus, it can have disastrous consequences in women of reproductive age group if contracted during pregnancy. The data about the prevalence of rubella infection in Bangladesh is sparse. This paper presented here, with the aim to ventilate the occurrence of rubella infection in the community and make aware doctors community about this viral infection burden that may have sometimes very disastrous consequences like many congenital birth defects. We are reporting several cases of German Measles occurring in Rajshahi city. TAJ 2010; 23(1): 106-108